Combining Two Models of Successful Information System Measurement - Pualam Dipa Nusantara; Nyoman Ayu Gayatri; Martin Suhartana (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This paper purposes is to measure successful of Academic Advisory information system by combining two models of information system measurement. DeLone & McLean IS Success Model use to measure the successful of system while COBIT framework is to measure system maturity level. Result of this research showed that the successful of Academic Advisory IS affected by User Satifaction, Quality of Service, Quality of System while Maturity level at 3.7. The result also showed there’s a relation between level of maturity system with the success of system.